Individual Changes in Respiratory Compliance Upon Immersion May Predict Susceptibility to Immersion Pulmonary Edema - Olivier Castagna; Arnaud Druelle; Guillaume Michoud; Thibaut Prevautel; Jean-René Lacour (SpringerOpen, 2023)
Abstract Background Immersion pulmonary edema (IPE) is a frequent diving accident, and it is the primary cause of hospitalization for young military divers during training. The objective of this study was to identify immersion-induced parameters predicting individual susceptibility to IPE. Methods Eighteen experienced male divers having completed at least 100 dives were recruited. Eight divers had previously been hospitalized for IPE (IPE), and the other ten had never developed IPE (non-IPE). The two groups were matched for age, BMI, and number of dives performed. Ventilatory function and overall compliance of the respiratory system (Crs) were measured on land and during head-out-of-water immersion. Subjects also performed 30 min of fin swimming in a channel at 33 m min−1. Following this exercise, the presence of extravascular lung water, revealed by ultrasound lung comets (ULC), was assessed. Results In the whole group, the decrease in Crs upon immersion correlated with the immersion-induced alterations to expiratory reserve volume, ERV (r 2 = 0.91; p < 0.001), inspiratory reserve volume, IRV (r 2 = 0.94; p < 0.001), and tidal volume, Vt, changes (r 2 = 0.43; p < 0.003). The number of ULC correlated strongly with immersion-induced changes in ventilatory function (r 2 = 0.818; p < 0.001 for ERV, r 2 = 0.849; p < 0.001 for IRV, r 2 = 0.304; p = 0.0164 for Vt) and reduced Crs (r 2 = 0.19; p < 0.001). The variations of ERV, IRV, and Crs at rest induced by head-out-of-water immersion and the number of ULC measured after swimming for 30 min were significantly greater in IPE subjects. Conclusion In the face of similar immersion stresses, the extent of alterations to ventilatory function and the number of ULCs were very different between individuals but remained statistically correlated. These parameters were significantly greater in divers with a history of IPE. Alterations to pulmonary function and, in particular, to pulmonary compliance induced by head-out-of-water immersion, through their effects on work of breathing appear to allow the identification of divers with a greater susceptibility to developing IPE. Measurement of these parameters could therefore be proposed as a predictive test for the risk of developing IPE.